(untitled) (Collection of scientific works «Modern structures of metal and wood», 2024)
The term «object reliability» is given in accordance with the current standards. The two main methods for determining the reliability of building structures are presented. Specific design features of spiral-fold silos and a brief history of their development are described. The results of experimental studies of spiral- fold silo structures are presented. The statistical characteristics of bulk materials are presented. A methodology for reliability analysis of metal spiral-fold silos based on the analysis of the strength reserve with consideration of the complex stress-strain state has been developed. This methodology was used to analyze the reliability of a silo with a capacity of 1020 m 3 . The silo structure was loaded with various bulk materials, the statistical characteristics of which were analyzed. The results of determining the main values of the parameters for the reliability analysis of the silo are presented in tabular form. In accordance with DBN B.1.2-14:2018, Table B.2, the recommended value of the safety characteristic (failure rate) β for the calculated silo (consequence class CC2, structural responsibility category A) should correspond to the value β=4,27, thus, the results of the calculations confirmed that the reliability of the considered silo is ensured. Based on the results, the plots of stress and safety characteristics depending on the variation of characteristics of wheat were constructed. The graphs showed that the stresses in the silo wall increase with an increase in the density and lateral pressure coefficient and decrease with an increase in the coefficient of friction against the walls. The graphs show a linear tendency to decrease the safety characteristic with increasing stresses in the silo wall. The general conclusion about the sufficient reliability of the structures of metal spiral-fold silos that were calculated according to current standards is proved.